2014
DOI: 10.1596/1813-9450-6759
|View full text |Cite
|
Sign up to set email alerts
|

Does Growth Generate Jobs in Eastern Europe and Central Asia?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…For this reason, we are careful to distinguish inflation and the coefficient of variation in output growth as separate, but overlapping, features of the macroeconomy. In addition to sectoral composition, inflation, and growth volatility, AriasVazquez et al (2012), Richter andWitkowski (2014), andMcMillan andRodrik (2011) also find that higher employment intensities are associated with lower natural resource rents, as natural resource extraction is not historically an employment intensive industry.…”
Section: Prior Cross-country Studies Of the Employment Intensity Of Gmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, we are careful to distinguish inflation and the coefficient of variation in output growth as separate, but overlapping, features of the macroeconomy. In addition to sectoral composition, inflation, and growth volatility, AriasVazquez et al (2012), Richter andWitkowski (2014), andMcMillan andRodrik (2011) also find that higher employment intensities are associated with lower natural resource rents, as natural resource extraction is not historically an employment intensive industry.…”
Section: Prior Cross-country Studies Of the Employment Intensity Of Gmentioning
confidence: 99%
“…For example, Richter and Witkowski (2014) find that higher export diversity is positively related to employment intensities, but others present mixed evidence as to the impact of openness, foreign direct investment, and terms of trade. In a review of empirical studies of growth and job creation, Basnett and Sen (2013) also conclude that the evidence on trade liberalization's impact is inconclusive.…”
Section: Prior Cross-country Studies Of the Employment Intensity Of Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors then examine the determinants of employment elasticity and conclude that structural and macroeconomic policies significantly affect employment elasticity. For their part, Richter and Witkowski (2014) analyze the employment response to output in a sample of Eastern Europe and Central Asia countries. It has been revealed that employment elasticity increased over time and doubled between 1995-2001 and 2002-2007.…”
Section: Studies On the Determinants Of Employment Elasticitymentioning
confidence: 99%
“…stages of economic (and thus financial) transition [21][22][23][24][25][26][27][28][29][30] in countries that decades ago still were part of a much more secluded economic sphere [31][32][33][34][35][36][37][38][39][40], and thus had thrived less, economically and financially, despite their mostly healthy base of human capital. One of the most recent and most comprehensive reports is by UNECE [41]; thus, providing a cutting-edge and neutral set of assessments and recommendations for countries with a similar structure as Russia.…”
mentioning
confidence: 99%